Flaw found in Unix/Linux admin tool - Mohamed, Arif (Computer Weekly, 2004)
Also affected is Webmin, a system administration tool that ships with Linux distributions such as Suse, Mandrake and Gentoo. Webmin contains Usermin functions, including the vulnerable web mail feature, Secunia said.